Comparing Dynamic Versus Pre‐Planned Combinations of Individual and Collaborative Learning in a Classroom Experiment. - Yang, Kexin Bella; Pan, Yiliu; Liu, Menghan; Rummel, Nikol; Aleven, Vincent (Journal of Computer Assisted Learning, 2026)
Background: Traditionally, combining individual and collaborative learning happens in a pre‐planned and synchronised manner where the whole class switches between activities at the same time. However, in an era where personalised learning is showing great promise, a more dynamic way of combining the two activities may lead to better learning outcomes and/or be preferred by teachers and students. Objective: The current study aims to study teachers' and students' perspectives on two ways of combining individual and collaborative learning, as well as compare their potential differences in learning outcomes. Methods: Working with 195 students in 13 middle‐school classes, we conducted an experimental study with two conditions: Dynamic and Standard. The Dynamic condition allows personalized, self‐paced, and real‐time pairing up of students as the need arises in class; in the Standard condition, by contrast, students switch between activities in a pre‐planned manner, which happens at the same time for everyone in the class. We examined students' learning outcomes as the primary dependent measure, complemented by analyses of process data and stakeholder perceptions. Results: This study provides one of the first empirical examinations comparing dynamic versus pre‐planned combinations of individual and collaborative learning in authentic classroom settings. By triangulating quantitative learning data with stakeholder insights, we provide valuable findings and design implications for researchers and educational technology practitioners. We found that both conditions supported significant learning gains, with the Standard condition showing greater collaboration efficiency. While learning outcomes were comparable, both teachers and students favoured the dynamic approach for its flexibility and pedagogical value. This study steps closer to the future of highly personalized smart classrooms that can address the unique needs of each student. Summary: What is currently known about this topic? ○Classes often switch between activities in a fixed, pre‐planned schedule.○Personalised learning approaches are becoming increasingly important.○Dynamically switching may support more flexible student learning.What does this paper adds? ○Compares dynamic and standard switching between activities.○Examines both learning outcomes and teacher–student perceptions.○Provides one of the first empirical tests of dynamic orchestration.○Shows that both methods support learning, but differ in experience.Implications for practice or policy ○Dynamic switching can support flexible pacing based on classroom needs.○Teachers may benefit from tools that enable real‐time student pairing.○Standard, fixed schedules may offer stronger collaboration structure.○Results point toward smart classrooms that adapt to each student.